THE USE OF FIX UP STRATEGY TO IMPROVE THE STUDENTS READING SKILL - Jihan Salsabila; Destri Wahyuningsih; Widi Syaftinentias (J-Shelves of Indragiri (JSI), 2026)
This research investigates the effectiveness of the Fix-Up Strategy in improving the reading skills of eleventh-grade students at SMAN 2 Rengat Barat. The study was conducted due to students’ difficulties in understanding reading texts, limited vocabulary mastery, and low participation during the reading process. Using a quasi-experimental design, the research compared an experimental class taught using the Fix-Up Strategy with a control class taught through conventional methods. Data were collected through reading pre-tests and post-tests and analyzed using the Independent Samples T-Test. The findings showed a significant improvement in the experimental class, with the mean score increasing from 53.61 to 84.86, while the control class improved from 48.14 to 68.71. The statistical analysis revealed a Sig. (2-tailed) value of 0.000, indicating that the Fix-Up Strategy had a significant effect on students’ reading skills. The study concludes that the Fix-Up Strategy not only improves students’ reading comprehension but also encourages students to become more active and independent readers.